90Factors associated with pneumococcal carriage in children and adults in Fiji, using four cross-sectional surveys. (2nd September 2021) - Neal, Eleanor; Nguyen, Cattram; Ratu, Felista Tupou; Dunne, Eileen; Kama, Mike; Ortika, Belinda; Boelsen, Laura; Kado, Joseph; Tikoduadua, Lisi; Devi, Rachel; Tuivaga, Evelyn; Reyburn, Rita; et al.
Abstract: Background: Pneumococcal disease is preceded by carriage of pneumococci. We describe factors associated with pneumococcal nasopharyngeal carriage in Fiji, using data from annual (2012-2015) cross-sectional surveys, pre- and post-introduction of ten-valent pneumococcal conjugate vaccine (PCV10). Methods: Infants (5-8 weeks), toddlers (12-23 months), children (2-6 years), and their caregivers participated. Pneumococci were detected using lyt A qPCR, with molecular serotyping by microarray. We used logistic regression to determine predictors of carriage and density. Results: There were 8, 109 participants. Pneumococcal carriage was associated with: years post-PCV10 introduction (global P <0.001), iTaukei ethnicity (aOR 2.74 [95% CI 2.17-3.45] P <0.001); young age (global P <0.001); urban residence (aOR 1.45 [95% CI 1.30-2.57] P <0.001); living with >2 children <5 years (aOR 1.42 [95% CI 1.27-1.59] P <0.001); poverty (aOR 1.44 [95% CI 1.28-1.62] P <0.001); and upper respiratory tract infection (URTI) symptoms (aOR 1.77 [95% CI 1.57-2.01] P <0.001). Factors associated with PCV10 and non-PCV10 carriage were similar to those associated with overall carriage. Additionally, PCV10 carriage was associated with PCV10 vaccination (0.58 [95% CI 0.41-0.82] P =0.002) and cigarette smoke exposure (aOR 1.21 [95% CI 1.02-1.43] P =0.031. Non-PCV10 carriage was not associated with years post-PCV10 introduction. Conclusions: Introduction of PCV10 reduced the odds of overall and PCV10 pneumococcal carriage in Fiji. ITaukei ethnicity was positively associated with carriage after adjustment for PCV10. Key messages: PCV10 introduction was associated with reduced odds of overall and PCV10 pneumococcal carriage in Fiji. Despite high and similar PCV10 coverage rates, iTaukei ethnicity is positively associated with pneumococcal carriage, compared with Fijian of Indian Descent populations.